Adaptive teaching based on gamification: a pedagogical strategy for formative assessment in higher education - Martins, Paulo Rodolfo de Oliveira; Negri, Rogerio Galante; Formiga, Jorge Kennety Silva; Bardini , Vivian Silveira dos Santos; dos Santos Galvão, Amanda Louisi; Bressane, Adriano (Educação On-line, 2022)
This study aims at introducing and assessing a pedagogical strategy for formative assessment in higher education. Under such purpose, successive quick tests are applied as soon as new topics of the course are introduced to students. Thereby, learning weaknesses are identified, from which in turn makes it the focus of review by the student. In order to assess the effectiveness of this pedagogical strategy, two case studies were carried out at different undergraduate courses. As a result, there was a significant performance gain by the students. In conclusion, based on the analysis of statistical significance, it was possible to verify that the proposed pedagogical strategy constitutes a promising alternative for formative assessment in higher education.